Fe-S Cluster Assembly in Oxymonads and Related Protists - Vacek, Vojtech; Novák, Lukáš V F; Treitli, Sebastian C; Táborský, Petr; Cepicka, Ivan; Kolísko, Martin; Keeling, Patrick J; Hampl, Vladimír (Molecular biology and evolution, 2018)
The oxymonad Monocercomonoides exilis was recently reported to be the first eukaryote that has completely lost the mitochondrial compartment. It was proposed that an important prerequisite for such a radical evolutionary step was the acquisition of the SUF Fe-S cluster assembly pathway from prokaryotes, making the mitochondrial ISC pathway dispensable. We have investigated genomic and transcriptomic data from six oxymonad species and their relatives, composing the group Preaxostyla (Metamonada, Excavata), for the presence and absence of enzymes involved in Fe-S cluster biosynthesis. None possesses enzymes of mitochondrial ISC pathway and all apparently possess the SUF pathway, composed of SufB, C, D, S, and U proteins, altogether suggesting that the transition from ISC to SUF preceded their last common ancestor. Interestingly, we observed that SufDSU were fused in all three oxymonad genomes, and in the genome of Paratrimastix pyriformis. The donor of the SUF genes is not clear from phylogenetic analyses, but the enzyme composition of the pathway and the presence of SufDSU fusion suggests Firmicutes, Thermotogae, Spirochaetes, Proteobacteria, or Chloroflexi as donors. The inventory of the downstream CIA pathway enzymes is consistent with that of closely related species that retain ISC, indicating that the switch from ISC to SUF did not markedly affect the downstream process of maturation of cytosolic and nuclear Fe-S proteins.
Keywords: molekulární evoluce; genom protozoální; Genome, Protozoan; Evolution, Molecular; proteiny obsahující železo a síru; Oxymonadida; fylogeneze; Phylogeny; Transcriptome; Iron-Sulfur Proteins; transkriptom